Core temperature and hydration status during an Ironman triathlon - Laursen, P. B.; Suriano, R.; Quod, M. Q.; Lee, H.; Abbiss, C. R.; Nosaka, K.; Martin, D. T.; Bishop, D. (British Journal of Sports Medicine, 2006)
Background: Numerous laboratory based studies have documented that aggressive hydration strategies (1-2 litres/h) are required to minimise a rise in core temperature and minimise the deleterious effects of hyperthermia on performance. However, field data on the relations between hydration level, core body temperature, and performance are rare.